(untitled) (Journal of International Studies, 2020)
The land locked and underdeveloped country of Laos presents a scenario in early 1960s that almost brought the world on the brink of a major war. Compared to the contemporaneous Berlin Wall Crisis and Cuban Missile crisis, the events in Laos had been pushed back by scholars without it receiving much attention. The Lao imbroglio was accentuated after the escalation of conflict in Vietnam, when Laos became a side show of the Vietnamese conflict. When the two superpowers, the United States of America (USA) and the Union of Soviet Socialist Republics (USSR)confronted each other in Laos, there was a serious international crisis. The present paper would explore ramifications of the crisis in Laos in the context of Cold War. It would analyze factors responsible for escalating the crisis and defusing of it afterwards. The role of superpowers, great powers, and regional powers would be discussed with their interests and motivations. The local actors who had different considerations and their response to the ongoing crisis would also to be projected. The internationalization of the crisis, particularly after it was linked with Vietnam War, aggravated the problem in Laos resulting in a delay in finding a solution to problem in Laos.